The prevalence and risk factors of sexually transmitted infections among correctional institution inmates in Manado, Indonesia - Niode, Nurdjannah Jane; Raranta, Hessyani; Purwanto, Diana Shinta; Mamuaja, Enricco Hendra; Tallei, Trina Ekawati (Journal of Pakistan Association of Dermatologists, 2024)
Background Correctional facilities are particularly vulnerable to the spread of sexually transmitted infections (STIs). This study aimed to test for syphilis, human immunodeficiency virus (HIV), and hepatitis B virus (HBV) in inmates at the Correctional Institution Manado, Indonesia, and to evaluate its associated risk factors. Methods 94 inmates underwent venereal disease research laboratory (VDRL), anti-HIV, and HBsAg testing. Data collection encompassed socio-demographic characteristics, risk factors including age, educational level, marital status, number of sexual partners, sexual orientation, condom usage, intravenous drug use, other drug administration methods, and blood sampling for screening purposes. Results Sociodemographics were predominantly marked by groups between 25–49 of age (63.8%), possessing an intermediate education (63.9%), married (46.8%), sexually monogamous (54.3%), identifying as heterosexual (95.7%), never using condoms (58.5%), abstaining from intravenous drug use (95.7%), and utilizing other drug types (64.9%). Among the participants, 12.8% tested positive for VDRL, 1.1% for anti-HIV, and 6.4% for HBsAg. Only one subject exhibited reactivity to both VDRL and HBsAg tests. There was a strong connection between marital status and HBsAg (p=0.007). Conclusion The prison environment offered insights into STI dissemination in a high-risk population, emphasizing that spread prevention needs informative and therapeutic measures.